2022
DOI: 10.1159/000526695
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Sequentially Bilateral Cochlear Implanted Children Who Speak Mandarin

Abstract: <b><i>Introduction:</i></b> Cochlear implantation is an effective treatment for children with deafness. Although the binaural effect of bilateral cochlear implantation on sound localization and speech perception in noisy environments has been demonstrated, the outcome and performance predictors of the second cochlear implant (CI2) remain uncertain for patients receiving sequential implantation. This study evaluated the hearing performance between the first cochlear implant (CI1), CI2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…These findings disagree with several previous studies. 6,7,22 Smulders et al 6 found that a long interval or advanced age at the time of implantations does not necessarily lead to a poor prognosis after CI2 implantation. Friedmann et al 7 revealed significant improvements in adolescents who underwent CI2 implantation at a mean age of 13.5 years and mean interimplant interval of 8.2 years.…”
Section: Discussionmentioning
confidence: 99%
“…These findings disagree with several previous studies. 6,7,22 Smulders et al 6 found that a long interval or advanced age at the time of implantations does not necessarily lead to a poor prognosis after CI2 implantation. Friedmann et al 7 revealed significant improvements in adolescents who underwent CI2 implantation at a mean age of 13.5 years and mean interimplant interval of 8.2 years.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the present study, it was found that bilateral CI patients had better expressive language performance. In the study conducted by Li et al 12 it was determined that bilateral cochlear implants performed simultaneously, especially in noisy environments, improved hearing performance and quality of life more than unilateral or sequential cochlear implant recipients. The results were similar to the findings in our study.…”
Section: Discussionmentioning
confidence: 99%